We can solve this system by elimination method. We can take
![\begin{gathered} 3x+2y+4z=11 \\ 2x-y+3z=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/f1ykvqnzbbja8tjvsw65cgg2gv0n6i0xsh.png)
and multiply by 2 the second equation:
![\begin{gathered} 3x+2y+4z=11 \\ 4x-2y+6z=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8d4o9fsmalfqofj3w3befg9i9fd1i1nkbh.png)
and add both equations:
![\begin{gathered} 7x+0+10z=19 \\ 7x+10z=19\ldots\ldots.(A) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/p7pvgbqbn3htqw23yiprdtcvk3g1sz253s.png)
We can do something similar with 2nd and 3rd equations:
![\begin{gathered} 2x-y+3z=4 \\ 5x-3y+5z=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/22gvg2ir4hp1mkzldcbs8mim4olmbkux2i.png)
but now, we can multiply by -3 the first one:
![\begin{gathered} -6x+3y-9z=-12 \\ 5x-3y+5z=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1di2i7v5d5t7kbbgm7wzx2o75l15726pjo.png)
by adding both equations, we have
![\begin{gathered} -x+0-4z=-13 \\ -x-4z=-13\ldots..(B) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/h428gsf7shac882fzre6qz2830jjoulcim.png)
we have removed y, then we have equation A and B with only x and z varaibles:
![\begin{gathered} 7x+10z=19 \\ -x-4z=-13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/c5pu3cp93aefeplee92voxehvqm1sl6jop.png)
by multiplying the second equation by 7 and adding to the first, we have
![\begin{gathered} 10z-28z=19-7(13) \\ -18z=19-91 \\ -18z=-72 \\ z=(-72)/(-18) \\ z=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/tz91p80o3voudwc1mz1jxcews2zele369a.png)
Hence, we have that z=4. Now we can substitute tthis value into -x-4z=13 in order to find x:
![\begin{gathered} -x-4(4)=-13 \\ -x-16=-13 \\ -x=-13+16 \\ -x=3 \\ \text{then,} \\ x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/fp20l3732eetfptqnxmiu0so5fgcg6n4v8.png)
Finally, we can substitute x=-3 and z=4 into the first original equation in order to find y:
![\begin{gathered} 3(-3)+2y+4(4)=11 \\ -9+2y+16=11 \\ 2y+5=11 \\ 2y=11-5 \\ 2y=6 \\ y=(6)/(2) \\ y=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/vd7wegrnecvy8wu8gp93xhb1w2ps13bhhk.png)
Hence, the solution is x=-3, y=3 and z=4.